The vespid fauna of Pakistan - Rafi, Muhammad Ather; Carpenter, James M.; Qasim, Muhammad; Shehzad, Anjum; Zia, Ahmed; Khan, Muhammad Rafique; Mastoi, Muhammad Ishaque; Naz, Falak; Ilyas, Muhammad; Shah, Mazafar; Bhatti, Abdul Rauf (Zootaxa, 2017)
This study provides the first annotated check list of the Vespidae of Pakistan. It is based on the National Insect Museum collection and various studies in Pakistan. Among 105 identified taxa, 77 species and 28 subspecies are recorded in the four subfamilies Eumeninae, Masarinae, Polistinae and Vespinae. Three new records for the fauna of Pakistan are added, namely Anterhynchium mellyi, Antepipona ovalis and Eumenes coronatus coronatus. Among the total, 12 species/subspecies are endemic to Pakistan, namely Ancistrocerus pakistanus, Antepipona luteipes, Antodynerus flavescens karachiensis, Celonites nursei, Cyrtolabulus karachiensis, Eustenancistrocerus (Parastenancistrocerus) baluchistanensis, Katamenes dimidiatus watsoni, Knemodynerus lahorensis, Leptochilus (Neoleptochilus) hina, Leptochilus (Neoleptochilus) mirificus, Leptochilus (Neoleptochilus) umerolatus and Tachyancistrocerus pakistanus. Antepipona varentzowi (Morawitz, 1896) and Polistes rothneyi quatei van der Vecht, 1968 were incorrectly reported from Pakistan.